Further Observations on the Genus Arthraxon (Poaceae) - Jain, S. K. (Indian Forester, 1981)
The taxonomy of severa1 species of Arthraxon is discussed. The species and varieties found in eastern India are enumerated. A detailed illustrated account of A. hispidus (1 bunb.) Makino is given.